Digital Inclusive Finance and Foreign Direct Investment: Regression Analysis Based on Spatial Econometric Models - Xu Yekai (Ilmu Inovasi Nusantara, 2024)
This study investigates the relationship between digital inclusive finance (DIF) and foreign direct investment (FDI) in China, using panel data from 31 provinces, municipalities, and autonomous regions from 2011 to 2022. The research employs a dual fixed spatial Durbin model to empirically analyze the impact of DIF on FDI and its spatial effects. The primary issue addressed in the study is how DIF influences FDI, both within a region and across neighboring areas. The main objective of the research is to evaluate the spatial clustering characteristics between DIF and FDI and to determine whether DIF significantly enhances FDI levels in a region. Furthermore, the study aims to understand the